2016
DOI: 10.1371/journal.pone.0161201
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Determines Increased Specific MicroRNAs Levels in Sera and HDL of Acute Coronary Syndrome Patients and Stimulates MicroRNAs Production in Human Macrophages

Abstract: We aimed to determine the levels of microRNAs (miRNAs) in sera and HDL of acute coronary syndrome (ACS) compared to stable angina (SA) patients with/without hyperglycemia, and evaluate comparatively the functional effect of these sera on the processing machinery proteins (Drosha, DGCR8, Dicer) and miRNAs production in human macrophages. MiRNAs levels in sera and HDL from 35 SA and 72 ACS patients and 30 healthy subjects were measured by using microRNA TaqMan assays. MiR-223, miR-92a, miR-486, miR-122, miR-125a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 38 publications
(43 reference statements)
5
35
0
2
Order By: Relevance
“…Monocytes and macrophages export specific miRNAs, including miR-223-3p, to HDL (52), which can be transferred to endothelial cells and exert an antiinflammatory effect on these cells (57). HDL miRNAs have been shown to be altered in CVD and diabetes (52,53,58,59). These findings support the functional importance of the LPP exRNA transport pathway and reveal the potential of HDL-associated miRNAs as biomarkers for cardiometabolic diseases.…”
Section: Biological Significance Of Exrna Transportsupporting
confidence: 57%
“…Monocytes and macrophages export specific miRNAs, including miR-223-3p, to HDL (52), which can be transferred to endothelial cells and exert an antiinflammatory effect on these cells (57). HDL miRNAs have been shown to be altered in CVD and diabetes (52,53,58,59). These findings support the functional importance of the LPP exRNA transport pathway and reveal the potential of HDL-associated miRNAs as biomarkers for cardiometabolic diseases.…”
Section: Biological Significance Of Exrna Transportsupporting
confidence: 57%
“…The mechanisms of increasing or decreasing circulating miRNA levels in the hyperglycemic state are still unknown. Simionescu et al (46) reported that hyperglycemia increased the levels of Drosha, DGCR8, and Dicer expression and several miRNAs (miR-223, miR-92a, miR-486, miR-122, miR-125a, and miR-146a) in human macrophages. Nishikawa et al (47) reported that hyperglycemia causes pathological changes in small vessels and results in tissue damage in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is a systemic metabolic condition, and the animal model of STZ-induced diabetes is characterized by disruption of pancreatic beta-cells, which cannot release insulin, leading to hyperglycaemia (Szkudelski, 2001). The overlap between serum and retinal expression of the focused set of dysregulated miRNAs in STZ diabetic mice would suggest that hyperglycaemia modifies miRNA expression at a systemic level (Ocłoń, Latacz, Zubel-Łojek, & Pierzchala-Koziec, 2016;Silambarasan et al, 2016;Simionescu et al, 2016). Moreover, circulating miRNAs could come from exosomes, released from several tissues, working as paracrine signalling molecules in hyperglycaemic conditions (Guay & Regazzi, 2013;Gupta, Bang, & Thum, 2010;Hashimoto & Tanaka, 2017).…”
Section: Bdnf Ppar-α Creb1 and Vegf Dysregulation In Diabetic Rementioning
confidence: 99%